Gronwall's conjecture for 3-webs with infinitesimal symmetries - Agafonov, Sergey I. [UNESP] (International Press of Boston, 2020)
We study non-flat planar 3-webs with infinitesimal symmetries. Using multi-dimensional Schwarzian derivative we give a criterion for linearization of such webs and present a projective classification thereof. Using this classification we show that the Gronwall conjecture is true for 3-webs admitting infinitesimal symmetries.